Enabling Knowledge Sharing within e-Government Back-Office Through Ontological Engineering - Brusa, Graciela (2007)
Nowadays, organizational innovation constitutes the government challenges for providing better and more efficient services to citizens, enterprises or other public offices. E-government seems to be an excellent opportunity to work on this way. The applications that support front-end services delivered to users have to access information systems of multiple government areas. This is a significant problem for e-government back-office since multiple platforms and technologies coexist. Moreover, in the back-office there is a great volume of data that is implicit in the software applications that support administration activities. In this context, the main requirement is to make available the data managed in the back-office for the e-government users in a fast and precise way, without misunderstanding. To this aim, it is necessary to provide an infrastructure that make explicit the knowledge stored in different government areas and deliver this knowledge to the users. This paper presents an approach on how ontological engineering techniques can be applied to solving the problems of content discovery, aggregation, and sharing in the e-government back-office. This approach is constituted by a specific process to develop an ontology in the public sector and an ontology-based architecture. In order to present the process characteristics, a case study applied to a local government domain is analyzed. This domain is the budget and financial information of Santa Fe Province (Argentine).